Anlotinib Alone or in Combination With Temozolomide in the Treatment of Recurrent High-Grade Glioma: A Retrospective Analysis - Yang, Qunying; Guo, Chengcheng; Lin, Xiaoping; Luo, Lili; He, Zhenqiang; Lin, Fuhua; Zhang, Ji; Chen, Yinsheng; Jiang, Xiaobing; Ke, Chao; Mou, Yonggao (Frontiers in Pharmacology, 2021)
Background Anlotinib is a multi-target anti-angiogenic agent. This retrospective study aimed to evaluate the efficacy and safety of anlotinib alone or in combination with temozolomide (TMZ) for the treatment of recurrent high-grade glioma (HGG). Materials and Methods The clinical data of patients with recurrent HGG treated with anlotinib alone or in combination with TMZ in our cancer center were collected and analyzed. Treatment response was evaluated according to the response assessment for neuro-oncology (RANO) criteria. Progression-free survival (PFS) and PFS at 6 months (PFS6m), overall survival (OS) and OS at 12 months (OS12m) were evaluated by Kaplan-Meier method and compared by log-rank test. Results Between November 2019 and December 2020, 31 patients with recurrent HGG (21 of grade 4 and 10 of grade 3) were enrolled in this study. Seventeen patients received anlotinib alone and 14 received anlotinib plus TMZ. All patients were heavily treated, and the median lines of previous treatments were 2 and the median Karnofsky score was 60. At the data cutoff date, the median PFS was 4.5 months and PFS6m was 43.5%. The median OS was 7.7 months and OS12m was 26.7%. The PFS6m and OS12m for 21 patients with grade 4 glioma was 40.2% and 27.9%, respectively. The tumor objective response rate (ORR) was 41.9% in all patients and 33.3% in patients with grade 4 glioma. No grade 3 or worse treatment-related adverse events were recorded during the treatment. Conclusion Anlotinib alone or in combination with TMZ showed encouraging efficacy and favorable tolerability in patients with recurrent HGG who had been heavily treated.